2013
DOI: 10.3390/cancers5020726
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ellagic Acid on Angiogenic Factors in Prostate Cancer Cells

Abstract: Background: Several natural antioxidants, including ellagic acid (EA), have been reported to have chemotherapeutic activity in vivo and in vitro settings. Cytochrome P450 (CYP) activity and synthesis of both epoxyeicosatrienoic acids (EETs) and 20-hydroxy-5,8,11,14-eicosatetraenoic acid (20-HETE), together with vascular endothelial growth factor (VEGF) and heme oxygenase system (HO) have emerged as important modulators of tumor growth and metastasis. Methods: The anti-angiogenic effects of EA were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 71 publications
5
41
1
Order By: Relevance
“…Previous studies support the current findings, where EA inhibited renal mRNA of MCP-1 and TNF-α in a STZ-diabetic mice [9] and downregulated NF-κB signaling pathways in a rat model of Crohn's disease [32]. Another explanation for renoprotection offered by EA is linked to the suppression of HO-1 that was elevated in the kidney, in this investigation, following CIS administration, an effect that is in line with the work of Vanella et al [33] in an in vitro model of prostate cancer. As an adaptive response after the surge of free radicals, nitroactive stress, and/or inflammatory cytokines, the upshot in HO-1 increases the antioxidant and antiinflammatory cellular defense systems via the production of bilirubin and carbon monoxide [34,35].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies support the current findings, where EA inhibited renal mRNA of MCP-1 and TNF-α in a STZ-diabetic mice [9] and downregulated NF-κB signaling pathways in a rat model of Crohn's disease [32]. Another explanation for renoprotection offered by EA is linked to the suppression of HO-1 that was elevated in the kidney, in this investigation, following CIS administration, an effect that is in line with the work of Vanella et al [33] in an in vitro model of prostate cancer. As an adaptive response after the surge of free radicals, nitroactive stress, and/or inflammatory cytokines, the upshot in HO-1 increases the antioxidant and antiinflammatory cellular defense systems via the production of bilirubin and carbon monoxide [34,35].…”
Section: Discussionsupporting
confidence: 92%
“…In this respect, EA has shown chemopreventive effects in rodent models of oral [105,289,290], esophagic [291,292], mammary [293,294], lung [295], prostatic [296], intestinal [297] and colon cancer [298,299]. Besides, the antiproliferative activity of both EA and urolithins on several tumor cell lines has been clearly demonstrated Table 3 [79,[300][301][302][303]. In contrast, the evidence of anti-hepatocarcinogenic effects of EA is still contradictory (Table 3).…”
Section: Hepatocellular Carcinoma (Hcc) Is a Malignant Tumor Arising mentioning
confidence: 85%
“…In this aspect, ellagic acid (EA), a naturally occurring antioxidant, has recently emerged as a promising anti-cancer agent (Vanella et al, 2013). Luca Vanella and colleagues (Vanella et al, 2013) have reported that EA had anti-proliferative and cytodifferentiating effects in prostate cancer cell types. A tight link between inflammation and colon cancer was reported (Klampfer, 2011).…”
Section: Impact Of Cellular Genetic Make-up On Colorectal Cancermentioning
confidence: 99%